2017
DOI: 10.1038/s41598-017-07884-4
|View full text |Cite
|
Sign up to set email alerts
|

The synchronous improvement of strength and plasticity (SISP) in new Ni-Co based disc superalloys by controling stacking fault energy

Abstract: It is a great challenge to improve the strength of disc superalloys without great loss of plasticity together since the microstructures benefiting the strength always do not avail the plasticity. Interestingly, this study shows that the trade-off relationship between strength and plasticity can be broken through decreasing stacking fault energy (SFE) in newly developed Ni-Co based disc superalloys. Axial tensile tests in the temperature range of 25 to 725 °C were carried out in these alloys with Co content ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 56 publications
(63 reference statements)
0
4
0
Order By: Relevance
“…MT is a kind of special deformation twin that has a thickness of 4-50 atom layers, which play an important role in the deformation mechanisms of low SFE superalloys. It is reported that MTs could synchronously improve the strength and plasticity by acting both as dislocation blockers and dislocation slip planes in Ni-Co-based superalloys during tensile tests [13]. It has been well documented that MTs were generally introduced by severe plastic deformation that applied high strain rate and deformation amount at a low temperature [25,26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MT is a kind of special deformation twin that has a thickness of 4-50 atom layers, which play an important role in the deformation mechanisms of low SFE superalloys. It is reported that MTs could synchronously improve the strength and plasticity by acting both as dislocation blockers and dislocation slip planes in Ni-Co-based superalloys during tensile tests [13]. It has been well documented that MTs were generally introduced by severe plastic deformation that applied high strain rate and deformation amount at a low temperature [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…In the low-SFE superalloys, it was proved that microtwins (MTs) could be introduced during tensile deformation [12]. Furthermore, the ultimate tensile strength and uniform elongation were improved synchronously because microtwinning was activated in superalloys with decreased SFE at 650 and 725 • C [13]. When deformation occurred at higher strains, nanograins (NGs) were found to be produced in the superalloys deformed at a high temperature and low strain rate, which resulted in higher flow stress [14].…”
Section: Introductionmentioning
confidence: 99%
“…The increased Co:Ni ratio decreases the stacking fault energy of the L1 2 ‐strengthened superalloys, which promotes stacking fault formation during room‐temperature deformation. [ 66 ] As a result of the high‐density stacking faults formation, both the tensile strength and uniform elongation can be simultaneously improved. Moreover, the outstanding strength‐ductility combination has also been achieved in the Co–28.8Ni–10.0Al–10.2Cr–2.1Ti–2.2Ta–2.1Mo–1.5Nb multicomponent Co‐rich alloy, which demonstrates a tensile strength over 1 GPa together with a uniform elongation over 20% at room temperature.…”
Section: L12‐strengthened Co‐rich Alloysmentioning
confidence: 99%
“…The high‐temperature tensile properties also benefit from the increased Co:Ni ratio. [ 66 ] The profuse microtwinning formation contributes to the improved work‐hardening capacity and associated enhanced ultimate tensile strength at high temperature (over 1.2 GPa at 704 °C). Similarly, a newly developed Co‐rich superalloy with a composition of Co–37.6Ni–4.1Al–8.8W–14.0Cr–1.5Ti–0.5Ta–0.028C–0.009B–0.05Zr (wt%) also exhibited an outstanding high‐temperature strength.…”
Section: L12‐strengthened Co‐rich Alloysmentioning
confidence: 99%
“…The National Institute for Materials Science of Japan successfully developed the TMW series Ni-Co-based superalloys first by reducing SFE [8]. Compared with the stronger cast-forged U720Li superalloy, the temperature-bearing capacity of this Ni-Co-based superalloy can be increased by 30 • C. The mechanical properties and structural stability of Ni-Co-based superalloys are better than those of the U720Li superalloy, which is expected to become a key material for hot-end components [9][10][11][12]. With the unstoppable trend of product miniaturization in many fields such as aerospace, the nuclear industry, weapons equipment, and energy, precise plastic forming technology of Ni-Co-based superalloy micro components is a key task that needs to be solved urgently.…”
Section: Introductionmentioning
confidence: 99%